The correlation between anti phospholipase A2 specific IgE and clinical symptoms after a bee sting in beekeepers - Matysiak, Jan; Matysiak, Joanna; Bręborowicz, Anna; Dereziński, Paweł; Kokot, Zenon J. (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction: Beekeepers are a group of people with high exposure to honeybee stings and with a very high risk of allergy to bee venom. Therefore, they are a proper population to study the correlations between clinical symptoms and results of diagnostic tests. Aim: The primary aim of our study was to assess the correlations between total IgE, venom- and phospholipase A 2 -specific IgE and clinical symptoms after a bee sting in beekeepers. The secondary aim was to compare the results of diagnostic tests in beekeepers and in individuals with standard exposure to bees. Material and methods: Fifty-four individuals were divided into two groups: beekeepers and control group. The levels of total IgE (tIgE), venom-specific IgE (venom sIgE), and phospholipase A 2 -specific IgE (phospholipase A 2 sIgE) were analyzed. Results: Our study showed no statistically significant correlation between the clinical symptoms after a sting and tIgE in the entire analyzed group. There was also no correlation between venom sIgE level and clinical symptoms either in beekeepers or in the group with standard exposure to bees. We observed a statistically significant correlation between phospholipase A 2 sIgE level and clinical signs after a sting in the group of beekeepers, whereas no such correlation was detected in the control group. Significantly higher venom-specific IgE levels in the beekeepers, as compared to control individuals were shown. Conclusions : In beekeepers, the severity of clinical symptoms after a bee sting correlated better with phospholipase A 2 sIgE than with venom sIgE levels.